Effect of Cinnamon Bark Oil (Cinnamomum burmannii) on the Properties of Whey-Based Cheese Edible Films - Hasana, Annisa Nada; Salsabila, Shafa; Melia, Sri; Juliyarsi, Indri (Jurnal Ilmu dan Teknologi Hasil Ternak, 2025)
The whey-based edible film has high hydrophilic properties that can affect product quality and the shelf life of packaged products. This study aims to determine the effect of the cinnamon bark oil (Cinnamomum burmannii) addition and the most effective concentration on the physical and chemical properties of edible film. The main material used in this research is whey, which was obtained from Keju Lasi in Agam Regency West Sumatera.The method used in this research was an experimental method employing a  Randomized Block Design (RBD) with 5 treatments and  4 replicates. The treatments in this study were cinnamon bark oil concentrations 0%, 0.2%, 0.4%, 0.6%, and 0.8%. The results showed that the concentration of cinnamon bark oil had a significant effect (p < 0.05) on the thickness of 0.13-0.20 mm, water vapor transmission rate of 4.39-2.69 g/m²/day, solubility of 73.18-66.73%, and color L* (24.48-32.22), a* (-1.76-(-4.28)), and b* (0.74-10.47), antioxidant activity 39.48 - 48.48%, hedonic quality test, color 4.86 (yellow) - 1.96 (dark yellow), aroma 4.40 (mild cinnamon aroma) - 1.52 (very strong cinnamon aroma), taste 4.18 (mild bitter) - 2.30 (strong bitter), and texture 3.24 (medium elasticity) - 2.64 (low elasticity). However, the addition of cinnamon bark oil gave no significant effect (p > 0.05) on the moisture content of 19.54-22.73%, and pH 5.63-5.39 whey-based edible film. This study concluded that the best treatment in this study was treatment 0.2% for the physical properties of whey edible film.